Promoting Critical Thinking, Communication Collaboration and Creativity (4C) in Teaching Speaking Using the Fishbowl Strategy - Cahyono, Slamet; Danim, Sudarwan (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
There has been a lot of talk about 21st-century skills for learning which are required for progressive learning in modern and effective ways. The essence of these skills includes Critical Thinking, Communication, Collaboration, and Creativity which are often referred to as the 4Cs of learning. English teacher has to focus to improve the students’ English proficiency and exploration of efficient ways of acquiring competence in the use of English for learning and the workforce in the future by implementing suitable and effective strategies in teaching.  One of them is Fishbowl.  It is a teaching strategy that helps students practice being contributors and listeners in a discussion. Students ask questions, present opinions, and share information when they sit in the “fishbowl” circle, while students on the outside of the circle listen carefully to the ideas presented and pay attention to the process, then the roles reverse. This strategy is especially useful when you want to make sure all students participate in the discussion, when you want to help students reflect on what a “good discussion” looks like, and when you need a structure for discussing controversial or difficult topics. This paper reveals an alternative strategy for the implementation of the 2013 curriculum in teaching speaking English.